Liquid and Thin-Layer Chromatography - Lewis, Simon; Lenehan, C. (Academic Press, 2013)
Liquid chromatography is a broad classification used to describe a variety of different chromatographic configurations that rely on the use of a liquid mobile phase. Paper, thin-layer, and classical column chromatography techniques, as well as high-performance liquid chromatography (HPLC) and ion chromatography, all belong to the class of liquid chromatography. These techniques are heavily used in forensic science to separate a wide range of analytes including, but not restricted to, illicit drugs, drugs, and drug metabolites in toxicology samples, explosives residues, and textile fiber dyes. A variety of separation mechanisms can be used within liquid chromatography; these include adsorption, ion-exchange, size-exclusion, affinity, and ion-pair formation. A discussion of these separation mechanisms can be found in Chromatography: Basic Principles. This article gives an overview of classical, high-performance, and thin-layer chromatographic techniques including experimental configurations and forensic applications.